Choral Masterpieces: Major and Minor - Tarling, Nicholas (Rowman & Littlefield Publishers, 2014)
In Choral Masterpieces: Major and Minor, historian Nicholas Tarling surveys the landscape of choral works, some standard masterpieces that are commonly performed by choruses around the world, others deserving a second, closer look. As noted in the foreword by Uwe Grodd , music director of the Auckland Choral Society, this work “is a collection of essays about a number of outstanding works, including Beethoven’s Miss Solemnis and Britten’s War Requiem, but he also invites attention to lesser masterpieces. If the choral movement, which includes both singers and listeners, is to survive, new works must be created and repertory expanded. The book is an easy and captivating read even if you are not a chorister.” Choral Masterpieces: Major and Minor features short essays on over 28 works, from major masterpieces such as Handel’s Messiah and Bach’s St. Matthew’s Passion to off-the-beaten path choral works such as Samuel Coleridge-Taylor’s Hiawatha and Frederick Delius’ A Mass of Life. Throughout, Tarling offers assessments that sparkle with unique insights and at the same time ground listener’s in the historical contexts of the work’s production and performance. Each work is transformed in Tarling’s able hands from musical work into a window into the mind and milieu of the composer. Choral Masterpieces: Major and Minor mixes choral mainstays with works that demand revisiting. Choral singers and their audiences, as well as choral societies and their directions and promoters, will find ample food for thoughts in these meditations on the choral tradition.